Quick-Skip Search Hybrid Algorithm For The Exact String Matching Problem (مجلة المنصور, 2022)
The string matching problem occupies a corner stone in many computer science fields because of the fundamental role it plays in various computer applications. Thus, several string matching algorithms have been produced and applied in most operating systems, information retrieval, editors, internet searching engines, firewall interception and searching nucleotide or amino acid sequence patterns in genome and protein sequence databases. Several important factors are considered during the matching process such as number of character comparisons, number of attempts and the consumed time. This research proposes a hybrid exact string matching algorithm by combining the good properties of the Quick Search and the Skip Search algorithms to demonstrate and devise a better method to solve the string matching problem with higher speed and lower cost. The hybrid algorithm was tested using different types of standard data. The hybrid algorithm provides efficient results and reliability compared with the original algorithms in terms of number of character comparisons and number of attempts when the hybrid algorithm applied with different pattern lengths. Additionally, the hybrid algorithm produced better quality in performance through providing less time complexity for the worst and best cases comparing with other hybrid algorithms.